1999
DOI: 10.1021/la981165c
|View full text |Cite
|
Sign up to set email alerts
|

Temperature-Programmed Desorption of Oxygen Surface Complexes on Acenaphthylene-Derived Chars:  Comparison with Oxygen K-Edge XANES Spectroscopy

Abstract: The interpretation of temperature-programmed desorption (TPD) data relating to the decomposition of oxygen surface complexes on carbonaceous materials is complex. Oxygen K-edge XANES spectroscopy was used to characterize a series of acenaphthylene-derived chars oxidized by either partial combustion or low-temperature oxygen chemisorption prior to their study by TPD. Evidence for the presence of mobile hydrogen species was provided by the observation that H2 and H2O were evolved at high temperatures during TPD.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2001
2001
2016
2016

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 49 publications
1
9
0
Order By: Relevance
“…A broad, weak HCN TPD peak was observed at 1285 K while the hydrogen peak was at 1270 K. The TPD profile of AD1073-B56, which has been subjected to partial combustion, displays a small HCN peak . Previous XANES studies have shown that partial combustion samples contain pyridone, carboxylic anhydride, and carbonyl groups. , AD1073 desorbs the largest amount of H 2 during pyrolysis in the temperature range 800−1350 K due to the growth of graphene layers in the graphitizable carbon (see Supporting Information) so that TPR has little effect on the evolution of nitrogen-containing species.…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…A broad, weak HCN TPD peak was observed at 1285 K while the hydrogen peak was at 1270 K. The TPD profile of AD1073-B56, which has been subjected to partial combustion, displays a small HCN peak . Previous XANES studies have shown that partial combustion samples contain pyridone, carboxylic anhydride, and carbonyl groups. , AD1073 desorbs the largest amount of H 2 during pyrolysis in the temperature range 800−1350 K due to the growth of graphene layers in the graphitizable carbon (see Supporting Information) so that TPR has little effect on the evolution of nitrogen-containing species.…”
Section: Resultsmentioning
confidence: 97%
“…The conversion of quaternary nitrogen to NOx under combustion conditions is a major issue. XANES showed that pyridone, carboxylic anhydride, and carbonyl groups were formed during the carbon combustion. , These groups appear to have little effect on desorption of nitrogen species from AD1073-B56 and GNA-B56. Kapteijn et al investigated the gasification of nitrogen-containing model chars where quaternary nitrogen was the major constituent, in CO 2 and O 2 .…”
Section: Resultsmentioning
confidence: 98%
“…[26][27][28] The interpretation of TPD data is complex because of the distribution of different environments for functional groups and surface group mobility is significant at high temperature. 29 The total CO2/CO ratios can be used quantitatively, while the identification of specific functional groups is semi-quantitative. 27 Carboxylic and lactones decompose to give CO2 in the temperature range 473 -923 K, while less acidic (phenol and carbonyl) and basic (pyrone) groups are desorbed mainly as CO or CO + CO2 in the temperature range 773 -1273 K. 27 CO desorption occurred at higher temperatures than the corresponding CO2 and reached a maximum at ~ 973 K. A small amount of NO was desorbed for the two lowest temperature treated carbons, due to the decomposition of small amounts of pyridine-N-oxide groups incorporated by the nitric acid oxidation procedure.…”
Section: Temperature Programmed Desorptionmentioning
confidence: 99%
“…Samples (5-10 mg) were treated in flowing helium, 99.9995% pure (5 ml min 21 , atmospheric pressure), at 20 K min 21 from 300 to 1700 K. Evolved gases were detected with a Leybold Quadrex 100 mass spectrometer using a differential pumping. External calibration was done by means of reference gas mixtures and signal shift was corrected by internal calibration with neon (1 vol.% in the carrier gas) [48]. The sample holder was an open spoon-shaped crucible with a U section 5 mm long.…”
Section: 8 Temperature-programmed Desorption (Tpd)mentioning
confidence: 99%